Masyarakat Desa dan Perangkat Digital - Onal Syafrizal (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
This article examines the rural portrait in the Acehnese society amidst the racist raciality of technology, where the increasing number of digitalisations in the village, the values of rural areas seem to be experiencing a decline or change unlike before. A smartphone or a mobile device that has been created as complex as possible to be multi-functional, can function as a mobile phone, as access to news, online games and so on. So that young people in the village, even even ua people are neglected because of it, so as to result in a rural identity gradually experiencing degradation or decline. The research method used is by means of observation, directly observing phenomena in the field and also combining them with data collected from various literature related to rural sociology. The results of these findings show, in fact there is something that needs to be taken care of behind the entry of digitalization of rural communities in Aceh, even though the rationality of this technology cannot be bent, it can be conditioned by maintaining tradition, village autonomy and village values amidst the impact of digitalization.